دور ومسؤولية مراقبي الحسابات في العراق تجاه الأفصاح الألكتروني للقوائم المالية (Journal of Accounting and Financial Studies ( JAFS ), 2010)
This research aims at shedding light on the electronic disclosure of the financial information under the condition of the development of this kind of disclosure all over the world , and its effect  on the job of auditing and accounting . It also aims to show the extent to which the observers of accounts are aware of their duties towards this kind of disclosure and to test the effect of some environment factors on the level of this awareness.To achieve the aims of the research has been divided in to four parts. The first one deals with mathadolge of the research. The second parts is devoted to the theoretical aspect of the research referring to the notion of electronical, disclosure its features and effect on the auditing job and the responsibility bounding of the account observer towards it. The coming part focuses on the experimental aspect in which a questionaire list has been prepared and then given to a number of account-observers in Iraq. The last part is related to the main findings which the research has reached at, then, a number of recommendations have been suggested depending on the pervious findings.